2015
DOI: 10.1149/2.1041507jes
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Pure Magnesium with Low Iron Content in 3.5 wt% NaCl Solution

Abstract: The microstructure and corrosion behavior of pure magnesium, with 25 ppm Fe but a high corrosion rate, have been studied in this work. It was found that Fe-rich particles, containing also Si, distribute non-uniformly in the Mg matrix and they are spaced at a distance of 100-1000 μm. Before the initiation of localized corrosion, Fe-rich particles play a key role in determining the overall corrosion behavior by supporting hydrogen evolution. During corrosion propagation, Fe-rich particles could be oxidized once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…In the areas where the pitting corrosion has not been initiated, needle-like crystalline precipitates can be found developed on the surfaces of both PEO and BTA-HNT-PEO coatings, indicating uniform degradation of the coating matrix due to the corrosion attack. Similar precipitates comprising a mixture of Mg(OH)2, MgO and MgCl2 have been observed by Yang et al[50] in the case of uniform corrosion of Mg in NaCl solutions. However, such needle-like corrosion products were not present on the surface of the HNT-PEO coating, indicating that the pitting corrosion could have played the major role in its degradation.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In the areas where the pitting corrosion has not been initiated, needle-like crystalline precipitates can be found developed on the surfaces of both PEO and BTA-HNT-PEO coatings, indicating uniform degradation of the coating matrix due to the corrosion attack. Similar precipitates comprising a mixture of Mg(OH)2, MgO and MgCl2 have been observed by Yang et al[50] in the case of uniform corrosion of Mg in NaCl solutions. However, such needle-like corrosion products were not present on the surface of the HNT-PEO coating, indicating that the pitting corrosion could have played the major role in its degradation.…”
supporting
confidence: 80%
“…However, after the PDP scan and subsequent immersion, |Z| f0 came to a level which was higher than that after 1 h. This is likely to be due to the formation of a deposited corrosion product at the sites of pitting corrosion induced by the anodic polarisation in the PDP test. It should be noted that irregularities in corrosion behaviour are commonly observed for pure Mg and Mg alloys in NaCl solutions and temporal increases in corrosion resistance could appear after few hours to several days of immersion, lasting for up to several hours until the breakdown of the deposited film of corrosion products occurs [13,50]. It is therefore conceivable that such periodic behaviour will persist for the samples with dramatically decreased during the fourth hour (Fig.…”
Section: Response To Damage Induced By Anodic Polarisationmentioning
confidence: 97%
“…Therefore, we deduce that impurity elements, such as Fe, may be the cause for the high corrosion rate of the reported Mg-Al alloys [27]. Effects of Fe in magnesium alloys have been studied and it is confirmed that Fe can significantly increase corrosion rate by forming Ferich particles in m agnesium alloys [30][31][32]. Generally, less than 9 wt% Al is alloyed in Mg in commercial Mg alloys [27,33].…”
Section: Galvanic Corrosion Testsmentioning
confidence: 79%
“…Once the potential has increased sufficiently, the original film undergoes breakdown and corrosion proceeds locally. As soon as this occurs the potential becomes relatively steady and hydrogen streams composed by very fine bubbles are observed at the interface between the silvery and the dark areas 8 .…”
Section: Introductionmentioning
confidence: 99%